2021
DOI: 10.3389/fgene.2021.694571
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Linc00284 Promotes Lung Cancer Progression by Regulating the miR-205-3p/c-Met Axis

Abstract: Lung cancer (LC) is a malignant tumor with the highest incidence and mortality rates worldwide. Linc00284, a long non-coding RNA, is a newly discovered regulator of LC. This study aimed to explore the role of Linc00284 in LC progression. Gene expression levels were detected by RT-qPCR and/or western blot analysis. Cell migratory and invasive capabilities were measured by wound healing and transwell assays. Subcutaneous xenograft models were constructed to examine tumor growth of LC cells. Data showed that Linc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This result was verified by assessment of the protein expression levels of p-MEK, p-ERK, p-mTOR, and p-STAT3, which are key targets in the downstream signaling pathway (Figure 6A,B). To further explore how c-MET protein expression levels were affected by 1 and 1a, we examined the mRNA expression levels of c-MET by RT q-PCR after compound treatment [37]. Intriguingly, c-MET mRNA levels in HEL cells were reduced in a dose-dependent manner with compound treatment, indicating that c-MET expression is subject to pretranscriptional regulation (Figure 6C); this indicates that c-MET and its downstream pathways are repressed, at least in part, through c-MET pretranscriptional regulation after treatment with 1 and 1a.…”
Section: Compounds 1 and 1a Antagonize The Mapk Signaling Pathway To ...mentioning
confidence: 99%
“…This result was verified by assessment of the protein expression levels of p-MEK, p-ERK, p-mTOR, and p-STAT3, which are key targets in the downstream signaling pathway (Figure 6A,B). To further explore how c-MET protein expression levels were affected by 1 and 1a, we examined the mRNA expression levels of c-MET by RT q-PCR after compound treatment [37]. Intriguingly, c-MET mRNA levels in HEL cells were reduced in a dose-dependent manner with compound treatment, indicating that c-MET expression is subject to pretranscriptional regulation (Figure 6C); this indicates that c-MET and its downstream pathways are repressed, at least in part, through c-MET pretranscriptional regulation after treatment with 1 and 1a.…”
Section: Compounds 1 and 1a Antagonize The Mapk Signaling Pathway To ...mentioning
confidence: 99%
“…In addition to activating the PI3K/AKT signaling pathway, as mentioned above, lncRNA LINC01510 can activate the classical MAPK signaling pathway by upregulating MET to promote EGFR-TKI resistance ( Pal et al, 2022 ). Moreover, other lncRNAs, such as Linc00284, FAM83A-AS1, and LINC00857, were revealed to mediate lung cancer progression through the regulation of MET ( Su et al, 2020 ; Sheng et al, 2021 ; Zhao et al, 2022 ), but their roles in EGFR-TKI resistance need to be further explored.…”
Section: Modulation Of Alternative Bypass Signaling Pathwaysmentioning
confidence: 99%
“…Previous studies showed that microRNAs (miRs), including miR-205-3p, a class of noncoding RNA molecules, act as potential markers for the progression of NSCLC [ 102 , 103 ]. A recent in vitro experiment has suggested that the Aβ precursor protein-binding family B member 2 (APBB2)-mediated activation of dysregulated miR-205-3p expression in different NSCLC cells, including H460, H1299, 95-D, and A549, resulted in activation of proliferation and inhibition of apoptosis in NSCLC cells [ 104 ].…”
Section: Pcs and Acns As Positive Modulators Of Human α7nachrmentioning
confidence: 99%
“…Taken together, nicotine-mediated activation of cell proliferation, migration, invasion, angiogenesis, and inhibition of apoptosis in NSCLC cells can be modulated when PCs and ACNs interact with the active site of α7AChR, displaying complex modulation of several transcription/growth factors via signaling pathways involved in α7nAChR activation, suggesting that such compounds may have a significant role in the treatment of NSCLC (Figure 2). Previous studies showed that microRNAs (miRs), including miR-205-3p, a class of noncoding RNA molecules, act as potential markers for the progression of NSCLC [102,103]. A recent in vitro experiment has suggested that the Aβ precursor protein-binding family B member 2 (APBB2)-mediated activation of dysregulated miR-205-3p expression in different NSCLC cells, including H460, H1299, 95-D, and A549, resulted in activation of proliferation and inhibition of apoptosis in NSCLC cells [104].…”
Section: Pcs and Acns As Positive Modulators Of Human α7nachrmentioning
confidence: 99%